KAJIAN EKSPERIMEN SISTEM PENDINGIN RUANGAN BERBASIS TERMOELEKTRIK DENGAN SUMBER ENERGI DARI PANEL SURYA - Taufiqurrahman, Muhammad (Universitas Majalengka, 2024)
Air conditioning system has a very important role in a building, this is to support activities in the building. Conventional cooling systems are based on vapor compression systems using refrigerant as the working fluid in the cycle. Commonly used refrigerant fluids have very high global warming and ozone destruction potential. Prolonged use of refrigerants will have negative impacts on the environment such as greenhouse gases and global warming. Through a photovoltaic (PV) system, solar light energy can be converted into electrical energy. Meanwhile, thermoelectric systems can convert temperature differences into electrical voltage differences or vice versa. Hybridization of the two systems can be used as an air conditioning system in buildings or other equipment. In this research, a prototype of a thermoelectric cooling system was produced with an energy source from solar panels, by determining the cooling temperature of a cube-shaped room with a side length of 30 cm at 26oC, the time required to reach this temperature was 18 minutes, data taken starting at 08.00, able to produce an average daily power from solar panels of 54.25 watts at each data collection. Meanwhile, the Coefficient of Performance of the cooling system in this study was 0.305. This system still cannot be compared with conventional cooling systems, but the cooling system in this research has the advantage of being a cooling system that is capable of producing cooling without using an electrical energy source from PLN.